Implementation of Virtual Reality Learning Media in Basic Social Studies Courses in the Primary School Teacher Education Program - Fahmi Syahrial, Mario (FKIP Unirow Tuban, 2025)
The purpose of this research is to examine the implementation of Virtual Reality (VR) as a learning media to enhance students' understanding in the course of Basic Concepts of Social Sciences (IPS) at Universitas PGRI Ronggolawe. This study employs a Pre-test Post-test One-Group model and involves 45 students from the PGSD2024 class X. The results show that students achieved significantly higher comprehension scores after using VR media; the average post-test score (75.20) was higher than the pre-test score (67.84). The results and discussion indicate a significant difference between the pre-test and post-test (p = 0.001), suggesting that Virtual Reality provides benefits for improving the understanding of basic IPS concepts. These findings support the use of VR technology as an innovative tool for interactive and in-depth learning..